Penetapan kadar flavonoid total ekstrak etanol daun bunga melati (Jasminum sambac (L.) Sol. ex Aiton) dengan spektrofotometri Uv-Vis - Hastri Kholifah; M. Pandapotan Nasution; Anny Sartika Daulay; Haris Munandar Nasution (Journal of Pharmaceutical and Sciences, 2023)
Traditional medicine uses plants with a natural ingredient content as its raw material. The bioactive compounds found in plants are secondary metabolites such as alkaloids, flavonoids, tannins, glycosides, steroids, and saponins. One of the plants containing secondary metabolite compounds is jasmine. This study aims to determine the chemical compounds contained in the ethanol extract and the total flavonoid content of the ethanol extract of jasmine leaves using the UV-Vis spectrophotometric method. The stages of this research included processing plant simplicia, making ethanol extract, examining characteristics, screening phytochemicals, and determining the total flavonoid content of the ethanol extract of jasmine leaves using the UV-Vis spectrophotometric method. Extract jasmine flower leaves by maceration method using 96% ethanol solvent; the extract obtained was concentrated using a rotary evaporator; then the total flavonoid content was determined using the UV-Vis spectrophotometry method. The research shows that the ethanol extract of jasmine flower leaves (Jasminum sambac (L.) Sol. ex Aiton) contains several secondary metabolite compounds, such as flavonoids, glycosides, alkaloids, saponins, steroids, and tannins. A number of steps were taken to find out how many flavonoids were in the ethanol extract as a whole. These included finding the maximum wavelength of quercetin, the operational time, making a quercetin calibration curve, and using UV-Vis spectrophotometry to determine how many flavonoids were in the extract. The analysis results reveal that the total flavonoid content in the ethanol extract of jasmine flower leaves is approximately 40.10911 ± 0.5878 mg QE/g.